Impact of Political Instability on the Reality of Iraqi Political Parties: A Study According to the Results of the 2018 Elections - Khalaf, Hamsa Kahtan (European Journal of Social Science Education and Research, 2021)
The Iraqi political parties had been affected since 2003 by the political pivotal transformations which happened according to the aftermaths of democratic elections , especially under the disruptions of American’s invasion that led in cooperation with its allies in April 2003 .So the social and political situations became ruling according to the new aspects of practicing the new stage of authority as compromise settlements and quota and ethno - sectarian distribution to be as following as compatible with theory of practicing the authority responsibilities(Power sharing ) as what happened now , besides to that all political democracy scene has greatly been distorted because of the instability penetrated within rebuilding the state and its institutions from the beginning as planned by an active powerful political forces . Many functions that are characterized by competitions among the political parties had changed the concepts of exercising democracy in a real way to be done an effective shape ,because of the political and social actors had different role ,which were being a reflection of another reality within the democracy’s process .So that all the situations had been complicated too much owing to the factors of political instability that influenced negatively on the framework of the state , especially the impacts of economic and social factors as of poverty, stagnation , ignorance and disease and another underdevelopment features which predominated over political and social retrogression levels . In addition to that the absence of an efficient administrative elites , which appeared recently under different conditions and circumstances .So it was became very obviously as we know precisely that democracy’s process in Iraq since 2003 was comprehensively undemocratic in practicing because the political forces have not democratic culture that encourage the dialogue to solve all pending problems , and have not abundant tolerance to accept the differences of others parties yet . The phenomenon of the political instability has divided into different varieties by which scattering among the addresses of suspicion and it definitely has a sectarian discourse dimension in case of dealing among each other . So these addresses and dialogues were being away from the political national conformity correctly , because of there was something like definitely as the exclusion and marginalization discourses in order to narrowing any active political party within the political process try to do pro – active role to settle all pending crises . Furthermore , the reality of political life has been under the continuous crises and conflicts over an authority along time not to gain gradually the outcomes of procurement during application the constitution clauses and valid laws , in order to preserving the political stability and to be done more far from the national unity fragmentation and the weakness of political institutions . Finally , we need too much time to reach into condition of stability , especially after opening anew spaces toward active real participation , and because there was a growing need for educated people who could administer the society and the state institutionally by existing strong government, and ultimately peoples will have ability to form new political governing elites later
Keywords: Impact of Political Instability on the Reality of Iraqi Political Parties: a Study According to the Results of the 2018 Elections